Plant cell biology : a practical approach - Hawes, C. R.; Satiat-Jeunemaitre, Béatrice (Practical approach series, 2001)
The 'post genomics' era has seen a surge in demand for the techniques of cell biology, to aid in interpreting the function and location of the cell's myriad proteins and macromolecules. This new edition of Plant Cell Biology provides a grounding in established procedures before guiding the reader through the field's most current techniques. It provides advanced undergraduates, postgraduates and research staff in the plant sciences with a uniquelycomprehensive guide to this rapidly expanding discipline.